The impact of abandoned pastoral settlements on plant and nutrient succession in an African savanna ecosystem - Muchiru, A.N.; Western, D.; Reid, Robin S. (Elsevier, 2009)
We detail the impact of abandoned traditional settlements (or bomas) on plant and nutrient succession in the Amboseli ecosystem, southern Kenya, over the course of a century. Plant and soil data were sampled on and around abandoned settlements. The term, ‘onsite’, refers to the area within the perimeter fence, ‘offsite’ to the area up to 200 m beyond the fence. Herbaceous standing biomass onsite increased in the course of succession to peak at twice offsite levels within two decades. Biomass remained elevated for six decades then dropped to the background levels at the limit of sampling distance. Plant species richness onsite increased rapidly in the course of succession, then stabilized on older bomas. Species composition changed throughout succession, with pioneer herbs and grasses giving way to boma-edge species and woody vegetation later in succession. Soil nutrients, including carbon, nitrogen, magnesium and phosphorus, were highly elevated on abandoned settlements. The various nutrients declined at different rates during the course of plant succession. Potassium, phosphorus and magnesium levels remained at twice offsite levels for over a century, creating islands of high fertility and high plant biomass in the savanna landscape. We conclude that the perturbation caused by shifting nomadic settlements creates localized nutrient and plant diversity hotspots in savanna ecosystems that remain distinct from the surrounding savanna for decades, possibly centuries.